Agro-terrorism? The causes and consequences of the appearance of witch’s broom disease in cocoa plantations of southern Bahia, Brazil - Caldas, Marcellus M.; Perz, Stephen (My University, 2013)
During the last few decades, the media, government leaders, scholars and national security analysts have all called attention to the potential threat presented by terrorism. In general, analyses have focused on the use of biological agents to kill or injure people. Consequently, the intentional contamination of crops by biological agents has received less attention in the media and counter-terrorism efforts when compared to possible attacks on civilian populations. However, in many countries, agricultural systems are one of the main economic sectors contributing to political stability, and the present literature lacks examples of terrorist attacks to agricultural systems. This paper is one of the first to discuss a concrete case of the appearance of a plant pathogen in an economically important region, possibly motivated by agro-terrorism. We highlight the differences between agro-terrorism and biocrime, and the causes and the consequences of the intentional introduction of pathogens as a means of causing economic damage. In particular, we argue that agro-terrorism and biocrime are both intentional criminal acts of introducing pathogens into agricultural systems to cause economic damage, but only agro-terrorism does so to advance a political agenda. Also, we argue that agro-terrorism can be difficult to distinguish from biocrime, and even if the intentional introduction of a pathogen is a political act of agro-terrorism, the consequences may or may not follow the desired script contemplated by the perpetrators, as pest outbreaks can entrain unintended economic, political and ecological consequences.
Keywords: Agro-terrorism; Biocrime; Cocoa economy; Social marginalization; Brazil